Strategy To Increase Fruit Chips Production Using the Line Balancing Method - Hakim, Oneilla Salsa Olga Nur; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to identify the grouping of work elements and evaluate the production efficiency of the fruit chips production process at Gapura, a home-based SME in Batu City, through the application of the line balancing method. Design/Methodology/Approach – This study employs a quantitative descriptive research design. Data were collected through observations, interviews, and documentation of the fruit chips production process. The line balancing method was applied to analyze work element allocation, production line efficiency, and balance delay, with the objective of identifying opportunities for improving operational performance. Findings – The results indicate that the existing production process has not implemented the line balancing concept, resulting in suboptimal workflow efficiency. The application of the line balancing method reduces balance delay by 15.7% and increases production line efficiency by 15.7%, demonstrating its effectiveness in optimizing work element allocation and improving production performance. Originality/Value This research is original in applying the line balancing method to a home-based fruit chips industry context. The findings offer practical value by demonstrating measurable improvements in efficiency and balance delay that can guide SMEs in optimizing their production systems.